Elevated Maternal Blood Lead Level - A Risk Factor for LBW - An Observational Study - Dhande, Leena; Waghmare, Kirankumar; Badhoniya, Neetu; Turankar, Avinash; Shetty, Ashwita (Journal of Nepal Paediatric Society, 2020)
Introduction: Lead exposure is common in women. Lead stored in bones is released during pregnancy and can potentially affect foetal growth. We conducted this study to estimate the effect of maternal blood Lead (BPb) status on Low Birth Weight (LBW) in newborns. Methods: 168 mothers were selected from Special Neonatal Care Unit (SNCU) and Postnatal care (PNC) wards of a tertiary care hospital from Central India and their BPb levels analysed by Graphite Furnace Atomic Absorption Spectrophotometer. Results: 22 (13.10%) mothers having BPb level ≥ 5μg/dL gave 23 births (one twins); of which 65.22% mothers delivered babies with birth weight < 2500gm (LBW) (p = 0.0007). The mean birth weight of newborns of mothers with high BPb levels was significantly lower by 269 gm (p = 0.0265). Mothers with BPb ≥ 5μg/dL delivered 39% premature babies as compared to 10 % mothers with BPb < 5 μg/dL (p < 0.003). Significantly more mothers exposed to kajal, nail polish, lipstick and paints had BPb levels ≥ 5μg/dL. Conclusion: Significant association is detected between maternal BPb and both LBW and prematurity in the given population.